Chromobox homolog 8 is a predictor of muscle invasive bladder cancer and promotes cell proliferation by repressing the p53 pathway. Issue 11 (25th September 2017) - Yuan, Gang‐jun; Chen, Xin; Lu, Jun; Feng, Zi‐hao; Chen, Si‐liang; Chen, Ri‐xin; Wei, Wen‐su; Zhou, Fang‐jian; Xie, Dan
Abstract : Chromobox homolog 8 (CBX8), also known as human polycomb 8, is a repressor that maintains the transcriptionally repressive state in various cellular genes, and has been reported to promote tumorigenesis. In the present study, we examined CBX8 expression in eight pairs of muscle invasive bladder cancer tissues and adjacent non‐tumor tissues, and found that CBX8 was frequently upregulated in muscle invasive bladder cancer tissues when compared to adjacent non‐tumor tissues. Analysis showed that high expression of CBX8 in 152 muscle invasive bladder cancer specimens was associated with progression of the T, N, and M stages ( P = 0.004, 0.005, <0.001, respectively). Furthermore, Kaplan–Meier survival analysis and log–rank test showed that muscle invasive bladder cancer patients with high CBX8 expression had a poor rate of overall survival ( P < 0.001) and 5‐year recurrence‐free survival ( P < 0.001) compared to patients with low CBX8 expression. High CBX8 expression predicted poor overall survival and 5‐year recurrence‐free survival in T and N stages of muscle invasive bladder cancer patients. Moreover, knockdown of CBX8 inhibited cell proliferation of urothelial carcinoma of the bladder both in vitro and in vivo . In addition, CBX8 depletion resulted in cell cycle delay of urothelial carcinoma cells of the bladder at the G2/M phase by the p53 pathway. The data suggest that high expression of CBX8 plays a critical oncogenic role in aggressiveness of urothelial carcinoma cells of the bladder through promoting cancer cell proliferation by repressing the p53 pathway, and CBX8 could be used as a novel predictor for muscle invasive bladder cancer patients. Abstract : CBX8 overexpression is possitively correlated with TNM staging of muscle invasive bladder cancer, and CBX8 promotes cancer cell proliferation by repressing the p53 pathway